Gambaran Status Gizi Balita di Posyandu RT 5 RW V Perumahan Villa Tembalang Bulusan, Tembalang, Semarang - Dian Nintyasari Mustika; Dewi Puspitaningrum (Universitas Muhammadiyah Semarang, 2015)
Posyandu is one of UKBM managed and organized from, by, for and with the community in the implementation of health development in order to empower people and provide convenience to the public in obtaining basic health care, especially in primary five priority programs including KB; KIA; Nutrition; Immunization and prevention of diarrhea and ARI with the aim of accelerating the reduction of maternal and infant mortality. The development of the state of community nutritioncan be monitored through the results recording and reporting program to improve community nutrition, as reflected in the results of weighing babies and toddlers every month at Posyandu. This study aims to describe the nutritional status of infants in Posyandu Villa Tembalang, Bulusan, Tembalang, S emarang. IHC is one of UKBM wicth managed from, by for and with the community in the implementation of health development in order This study is a descriptive study use the cross sectional design. The data was obtained by the population as much as 43 basis toddler with the criteria according to the study. The sample in this study was children aged 0 - 60 months. The sampling technique used in this study is total sampling, because all of the population component was used as the samples..The average age of the children is 40 months, with a minimum of age is one month and maximum is 59 months. The average weight of under five years old children is 13.023 kg, with astandard deviation is 3.5913kg. The average height of under five years old children is 92.123 cm with a standard deviation is 13.7491 cm. The mode of children;s height is 94.000 cm. The average Z score of index weight by height is -0.47 SD 1.45 SD, is included in the normal nutritional status. The average Z score of index height by age is 0.43 SD 3.43 SD, is included in the normal nutritional status. The average Z score of index weight by age is -0.13 SD 2.14 SD , is included in the good nutritional status. The average Z score of BMI by age is 4,68 SD 0,766 SD, is included in the normal nutritional status.The nutritional status of under five years old children at RT 5 RW V Housing Villa Tembalang, Bulusan, Tembalang is normal based on index of weight by height, height by age andBMI by age. The nutritional status of under five years old children is good based on index of weight by age.Keywords: The under five years old children, Nutritional Status